Understanding the concerns of teachers about leveraging mobile technology to facilitate outdoor social inquiry learning: the EduVenture experience. Issue 2 (17th February 2016) - Jong, Morris Siu-yung; Tsai, Chin-Chung
ABSTRACT: Our work is within the context of the ubiquitous discussion about adopting mobile devices to offer school-age students new learner-centric learning opportunities. Leveraging location-based context-aware mobile technology, based on the theoretical foundation of constructivist learning, we have developed EduVenture, an integrated mobile learning system by which teachers can facilitate students pursuing outdoor social inquiry learning in social and humanities education (namely, Liberal Studies in Hong Kong). This paper reports on our study in which we investigated 302 in-service Liberal Studies teachers' concerns about adopting EduVenture in practice with the Stages of Concern model, in terms of five categorical concerns – Evaluation, Information, Management, Consequence, and Refocusing . Results reveal that their Management concern was the most intense. The findings not only offer us critical insights into formulating more articulated interventions for better supporting teachers' adoption of EduVenture in schools, but they also provide a useful reference for researchers and practitioners who are pursuing work on integrating mobile learning into school education.